High-Performance PCR for Alleles Discrimination of Chromo-Helicase-DNA Binding Protein (CHD1) Gene in Bird Sexing - Marcello Tagliavia; Valentina Catania; Giacomo Dell’Omo; Bruno Massa (Biology, 2023)
Genetic analyses aiming at assessing the presence of specific sequences or alleles are often carried out by PCR. Sexing of most birds is nowadays based on PCR with “universal” primers and relies on the assessment of the presence of the sex-linked CHD1-Z and -W alleles. The entire workflow is relatively time-consuming, especially for batch analyses, whereas methods that allow carrying out the entire procedure in a short time are highly desirable. The only method for outdoor analyses reported so far relies on LAMP; however; it fails to work properly in Procellariiformes. Besides improving the LAMP test; we have developed a PCR-based DNA amplification procedure (named high-performance PCR); whose unique features allow it to outperform standard PCR; making possible the direct, in-tube visual reading of results. We tested it with specifically designed Procellariiformes-targeted primer sets for rapid sexing of the birds using fluorimetric detection. The protocol, combined with rapid DNA extraction, allows for fast reading of results without electrophoresis within less than 1 h from sampling. The technique could be extended to other species, as well as to many other applications.